Inserção do ligamento cruzado anterior: novos conceitos - Janovsky, Cesar [UNIFESP] (2016)
Introduction: Although numerous anatomical studies about the ACL structure and attachments have been performed, these studies have not reached a consensus on the ACL footprint. Objectives: Investigate the existing controversy regarding the morphology of the tibial anterior cruciate ligament (ACL) insertion (footprint) and confirm histologically that the tibial ACL footprint is not completely filled with ligament tissue. Methods: Tibial ACL footprints were dissected from eighteen fresh-frozen cadaveric knees (all male, 68.8±5.4 years old (range 55-80), weight 78± 6.6 kg range 45-93). The tibial ACL insertion was observed and this area was longitudinally divided into four parallel slices (0-25%, 25-50%, 50-75% and 75-100%), were embedded in paraffin wax and then stained with H&E, alcian blue and picrosirius-polarization. The specimens were measured using the microscope to determine the distances of ACL ligament tibial insertions. Results: The eighteen evaluated knee specimens confirmed the finding of a C-shaped tibial insertion of the ACL. The measurements showed that the ligament occupied only 30.8% of the complete insertion. The remaining area was filled with synovial tissue, demonstrating histologically the C-shape. Conclusions: Our study confirmed macroscopically the ACL ?C-shaped? tibial insertion and showed histologically that synovial tissue fills the major part of the footprint.